2022
DOI: 10.3390/bs12090334
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Theory of Planned Behavior in Explaining the Energy-Saving Behaviors of High School Students with Physical Impairments

Abstract: People with physical impairments can help solve energy problems by participating in diverse energy-saving behaviors, such as switching off lights or turning off an air conditioner when not in use; however, they may struggle to participate in some behaviors due to mobility impairments. This study aims to examine factors that impact the energy-saving behaviors of high school students with physical impairments. The theory of planned behavior (TPB) was used to test whether attitudes towards energy-saving behaviors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…It is considered as a behavioral outcome indicator in numerous theories, including TPB [ 36 ]. Intention has also been suggested as the best predictor of PEB [ 38 ] and energy-saving behavior [ 15 , 54 ] in past studies. Mixed study models have also considered it in connection to self-determination [ 55 ] and personal norms [ 56 ] in the context of energy conservation at work [ 21 ].…”
Section: Background and Hypothesis Developmentmentioning
confidence: 99%
See 3 more Smart Citations
“…It is considered as a behavioral outcome indicator in numerous theories, including TPB [ 36 ]. Intention has also been suggested as the best predictor of PEB [ 38 ] and energy-saving behavior [ 15 , 54 ] in past studies. Mixed study models have also considered it in connection to self-determination [ 55 ] and personal norms [ 56 ] in the context of energy conservation at work [ 21 ].…”
Section: Background and Hypothesis Developmentmentioning
confidence: 99%
“…Multiple studies on conservation behaviors have accordingly recently applied the TPB in both organizational and domestic settings [ 37 ]. In most studies, subjective norm has been found to be the parameter that mostly affects intention to act pro-environmentally [ 38 , 40 ] and to conserve energy [ 54 ] in the TPB model. However, in other studies subjective norm had no direct effect on pro-environmental behavioral intentions [ 41 ].…”
Section: Background and Hypothesis Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…484.2 -1037.6 kWh/year/household (Jareemit and Limmeechokchai 2019). Energy-saving behaviors are widely promoted as a solution to growing energy-related problems (Suntornsan, Chudech, and Janmaimool 2022). However, as concluded by Sony and Mekoth (2018), electricity-saving behavior "represents a significant untapped potential".…”
Section: Introductionmentioning
confidence: 99%